Implementasi Sosialisasi Pasar Modal Syariah untuk Meningkatkan Minat Investor Muda dalam Berinvestasi - Zulia Almaida Siregar; Zulaini Masruro Nasution; Ika Okta Kirana; Asmarani Nasution; Fitri Rizki (Jurnal Inovasi Akuntansi (JIA), 2023)
Investments are mu'amalah activities that are highly recommended in Islam, therefore the sharia capital market is present as a means of investment for Muslims who want to invest in accordance with sharia principles. The purpose of this study was to determine the extent of the implementation of socialization carried out by related parties in influencing the interest of young people in this case students at STIKOM Tunas Bangsa Pematangsiantar to invest in the sharia capital market. This type of research is field research (field research) and the nature of the research is descriptive qualitative. The data collection techniques used are interviews and documentation and data analysis techniques using inductive thinking. The results showed that the implementation of syrai'ah capital market socialization among young people greatly influenced interest and increased motivation to invest in the sharia capital market. The implication is that they invest in shares in the sharia capital market, this is influenced by the perceptions they have about an established future, a person who has good financial intuition, a firm attitude in making decisions in building individual economies in the future, strong motivation to invest for personal welfare and service.